Metro Manila Water Security Study - World Bank (Washington, DC, 2014)
The metropolitan waterworks and sewerage system (MWSS) services the water supply and sewerage requirements of Metro Manila including the Province of Rizal and parts of Cavite, an area composed of the estimated 15 million residents in one of the fast growing urban centers in the world. In order to secure the water supply for Metro Manila, some alternative water sources, that is Laguna Lake, Wawa, Kaliwa, Kanan, and Agos rivers, and others have been identified and studied since 1970s. In view of this, the MWSS has requested to the World Bank Group for the technical assistance to identify the alternative water sources to meet growing water demand in Metro Manila. The study was started in July 2011 to: (a) review previously executed studies and proposals for developing alternative water sources; (b) assess non-revenue water (NRW) reduction projects; and (c) provide updated and comprehensive advice to support water security enhancing initiatives in Metro Manila. The study was completed in July 2012 and the final report was submitted to MWSS and the World Bank. In this context, this report is organized as follows: chapter one gives introduction; chapter two presents socio-economic condition of study area; chapter three presents current water supply system and development; chapter four presents review and update of water demand projection; chapter five focuses on alternative water sources; and chapter six presents road map.